Intelligent context retrieval and management for services in the Internet of Things. (30th July 2013) - Cadenas, Alejandro; Baladron, Carlos; Aguiar, Javier M.; Carro, Belén; Sánchez–Esguevillas, Antonio
Information processing about a user's situation (or user's context) is one of the most significant paradigms in nowadays end user services development, supporting ambient intelligence, or applications that are able to react smartly to the condition of users and their surroundings. In the Internet of Things, where a plethora of connected devices produces and consumes information, there are many actors who will play the roles of context providers and context consumers. However, in a global environment, acquisition, processing and consumption of user's context information would be much easier if performed in a controlled and ordered fashion within an information exchange framework. In this paper, a proposal for a Convergent Context Enabler (CCE) is described and specific details are provided about the user's context processing and the interfaces designed to support the architecture. Finally, a use case of context–aware services in the Internet of Things is presented and analysed in detail.